Association Between Weight Status and Rate of Cognitive Decline: China Health and Nutrition Survey 1997-2018 - Lynch, David H; Howard, Annie Green; Tien, Hsiao-Chuan; Du, Shufa; Zhang, Bing; Wang, Huijun; Gordon-Larsen, Penny; Batsis, John A (The journals of gerontology. Series A, Biological sciences and medical sciences, 2023)
There is a close relationship between weight status and cognitive impairment in older adults. This study examined the association between weight status and the trajectory of cognitive decline over time in a population-based cohort of older adults in China. We used data from adults aged ≥55 years participating in the China health and nutrition survey (1997-2018). Underweight (body mass index [BMI] ≤ 18.5 kg/m2), normal weight (18.5-23 kg/m2), overweight (23-27.5 kg/m2), and obesity (BMI ≥ 27.5 kg/m2) were defined using the World Health Organization Asian cutpoints. Global cognition was estimated every 2-4 years through a face-to-face interview using a modified telephone interview for cognitive status (scores 0-27). The association between BMI and the rate of global cognitive decline, using a restricted cubic spline for age and age category, was examined with linear mixed-effects models accounting for correlation within communities and individuals. We included 5 992 adults (53% female participants, mean age of 62 at baseline). We found differences in the adjusted rate of global cognitive decline by weight status (p = .01 in the cubic spline model). Models were adjusted for sex, marital status, current employment status, income, region, urbanization, education status, birth cohort, leisure activity, smoking status, and self-reported diagnosis of hypertension, diabetes, or Myocardial Infarction (MI)/stroke. In addition, significant declines by age in global cognitive function were found for all weight status categories except individuals with obesity. In a cohort of adults in China, cognitive decline trajectory differed by weight status. A slower rate of change was observed in participants classified as having obesity.